THE CORRELATION BETWEEN READING MOTIVATION AND READING COMPREHENSION OF THE THIRD YEAR STUDENTS OF SMPN 12 PEKANBARU - Luis, Vida Hardianty Putri; ', Hadriana,Ph. D; ', Erni, S.Pd., M.Hum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This correlational study is aimed to find out the correlation between reading motivation and reading comprehension of the third year students of SMPN 12 Pekanbaru. The sample was chosen by using cluster random sampling as many as 39 students. The instrument used in this study was questionnaire and test; reading motivation questionnaire and reading comprehension test. Reading motivation questionnaire is used to know the students’ reading motivation while reading comprehension test is used to find out the students’ ability in understanding a text. The obtained data were assessed by using Product Moment’s formula and analyzed by using SPSS 21.0 for windows. Based on the data analysis, it shows that there is moderate, significant and positive correlation between grammar mastery and reading comprehension of the third year students of SMPN 12 Pekanbaru. Therefore, it answered the research question that there is a correlation between reading motivation and reading comprehension.Key words: correlation, reading motivation, reading comprehension